On the Right to the Protection of Persons in Respect of Whom a Preliminary Investigation Is Conducted - Kirill A. Naumov (Сибирское юридическое обозрение, 2016)
The article examines the procedural status of the person in respect of whom an investigation is conducted of a report of crime in the manner prescribed by article 144 of the Criminal Procedure Code of the Russian Federation. The order of the realization of the right to protection under a criminal investigation is studied. The problem of correlation of the status of lawyer and defender is considered.